Non‐invasive fibrosis markers are associated with mortality risk in both general populations and non‐alcoholic fatty liver disease patients. Issue 1 (8th October 2020) - Mao, Xianhua; Liu, Zhenqiu; Shi, Oumin; Yu, Kangkang; Jiang, Yanfeng; Jin, Li; Zhang, Tiejun; Chen, Xingdong
Abstract : Aim: We assessed the correlations between non‐invasive fibrosis scores and mortality in both the general population and non‐alcoholic fatty liver disease (NAFLD) patients. Methods: We used data from the US National Health and Nutrition Examination Survey 1988–2014. The NAFLD fibrosis score (NFS), Fibrosis‐4 index (FIB‐4) score, aspartate aminotransferase to platelet ratio index (APRI) score, and Forns index score were calculated at baseline. The associations of these scores with the risk of mortality were determined using additive Cox proportional hazard models. The area under the receiver operating characteristic curve (AUROC) was used to study the predictive capacity of each scoring system. Results: A total of 44 508 participants were included; among them, 9721 deaths occurred during a mean follow‐up of 12.5 years. A "J"‐shaped correlation pattern was observed for both the FIB‐4 and APRI scores. A "U"‐shaped correlation pattern was observed for both the Forns index and NFS. Similar correlation patterns were observed in 1955 NAFLD patients. For overall mortality, the AUROC values of the selected fibrosis scores were comparable between general population and NAFLD patients. The superior predictive capacity was found for FIB‐4, with AUROC of 75.03% (95% confidence interval, 70.91% to 79.82%) in general population and 75.32% (95% confidence interval, 69.43% to 80.11%) in NAFLD patients, respectively. Conclusions: Non‐linear associations were shown between the fibrosis scoring systems and mortality risk. These scores could serve as indicators for mortality in people with or without NAFLD.